Analysis of polypharmacy in elderly patients with decreased kidney and liver function: Case Report - Rina Widiyawati; Khoirul Anam; Nur Oktafiyani; M. Hari Pristantiningtyas; Herya Putra Dharma; Muhammad Muchlis; Jainuri Erik Pratama; Fauna Herawati; Adji Prayitno; Marisca Evalina Gondokesumo (Jurnal Teknologi Laboratorium)
Elderly patients are at a high risk of developing chronic diseases, including cardiovascular disease, cancer, dementia, and diabetes. Additionally, many elderly individuals experience multimorbidity, having more than one chronic condition, contributing to the phenomenon of polypharmacy. This case report aims to analyze polypharmacy therapy in elderly patients with concurrent decreased kidney function and elevated liver enzymes. Polypharmacy in elderly patients with decreased kidney and liver function necessitates a comprehensive study to assess both its benefits and potential side effects. Monitoring should be implemented to detect any emergence of side effects or drug interactions resulting from the prescribed therapy. According to the 2023 Beers Criteria, elderly patients with reduced kidney function face an elevated risk of drug-related side effects, potentially leading to prolonged hospital stays and increased medical costs.